Progressive Collapse in Multi-Storey Steel Frames: The Effect of Varying Column Spacing - JANSSENS, VICTORIA MARIA; O'DWYER, DERMOT WILLIAM (My University, 2011)
Following the collapse of the Ronan Point apartment tower, provisions to minimise the potential for progressive collapse were introduced in design codes for the first time. In recent years, the increased threat of terrorism has highlighted the importance of such robustness requirements. This paper presents a methodology to assess the extent of damage to a multi-storey structure following localised collapse. This is accomplished through the design of an algorithm, based on the notional element removal method. By systematically considering the effects of damage to all members in a structure, this algorithm can be used as both a design and an analysis tool to identify whether a structure is unduly sensitive to the effects of localised damage. This paper describes the key features of this analysis program. Additionally, the results of a study to determine the effect of column spacing on the response of a damaged structure are presented.
11th International Conference on Applications of Statistics and Probability in Civil Engineering
PUBLISHED
Keywords: Ronan Point apartment tower; Ronan Point apartment tower